2020
DOI: 10.1075/jhl.18038.cat
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic assessment of the Indo-Aryan Inner–Outer Hypothesis

Abstract: This paper uses a novel data-driven probabilistic approach to address the centuryold Inner-Outer hypothesis of Indo-Aryan. I develop a Bayesian hierarchical mixedmembership model to assess the validity of this hypothesis using a large data set of automatically extracted sound changes operating between Old Indo-Aryan and Modern Indo-Aryan speech varieties. I employ different prior distributions in order to model sound change, one of which, the logistic normal distribution, has not received much attention in lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This spatial flexibility is achieved by reducing the complexity of the clustering: in order to keep the model simple and clustering tractable, we require that one language belongs to one area at a time and that areas cannot overlap. Complementary statistical models have shown that these assumptions can be relaxed, for example when the spatial influence is defined on extra-linguistic grounds [ 69 ], when clustering is applied to languages in a single family [ 28 , 29 , 70 , 71 ] or when it is applied to recover unspecified shared ancestry [ 72 ]. In future work, it will be interesting to explore whether statistical inference with is still tractable when the model supports probabilistic assignments of languages to areas and allows areas to overlap, while still inferring areality from the data rather than predicting it from extra-linguistic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This spatial flexibility is achieved by reducing the complexity of the clustering: in order to keep the model simple and clustering tractable, we require that one language belongs to one area at a time and that areas cannot overlap. Complementary statistical models have shown that these assumptions can be relaxed, for example when the spatial influence is defined on extra-linguistic grounds [ 69 ], when clustering is applied to languages in a single family [ 28 , 29 , 70 , 71 ] or when it is applied to recover unspecified shared ancestry [ 72 ]. In future work, it will be interesting to explore whether statistical inference with is still tractable when the model supports probabilistic assignments of languages to areas and allows areas to overlap, while still inferring areality from the data rather than predicting it from extra-linguistic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…I am entirely neutral with respect to this issue. For further discussion, see Cathcart (2020), who finds some evidence for this grouping using statistical methods, although it is not entirely conclusive.…”
Section: Two New Indo-aryan Case Studiesmentioning
confidence: 99%
“…Some of these sources have been used in previous work on South Asian historical linguistics, e.g. Cathcart and Rama (2020); Cathcart (2019bCathcart ( ,a, 2020-this is the first attempt to consolidate them. Note some previous work in this direction: while the SARVA project (Southworth, 2005) did not reach fruition, a searchable database of Dravidian cognates was developed by Suresh Kolichala under its auspices.…”
Section: Jambu Etymological Databasementioning
confidence: 99%